PERAN SUKU BUNGA DALAM MEMODERASI PENGARUH SOLVABILITAS, LOAN TO DEPOSIT RATIO DAN NON PERFORMING LOAN TERHADAP PROFITABILITAS PADA BANK UMUM KONVENSIONAL PERSERO YANG TERDAFTAR DI OTORITAS JASA KEUANGAN PADA TAHUN 2015-2022 - Ardiansyah, Johan Putra Pradana; Sari, Lita Permata; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2024)
Banks are companies that operate in the financial services sector, acting as intermediaries between people who need funds and people who have funds. The purpose of this study was to analyze and test the role of interest rates in moderating the effect of Solvency, Loan Deposit Ratio and Non-Performing Loans on Profitability. The method used in this research is descriptive quantitative. The population in this study is a Conventional Commercial Bank registered with the Financial Services Authority in 2015-2022. Purposive sampling is the sampling technique in this study. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of hypothesis testing using a statistical application, Smart PLS 3.0, the results showed that Solvency has a significant negative effect on Profitability, Loan Deposit Ratio has a negative but insignificant effect on Profitability, and Non-Performing Loan has a significant negative effect on Profitability. Interest rates negatively but not significantly moderate the effect of Solvency on Profitability. Interest rates insignificantly moderate the effect of Loan Deposit Ratio on Profitability. Interest rates insignificantly moderate the effect of Non-Performing loans on Profitability.